Eksistensi Ritus Gawe Pati Pada Masyarakat Wetu Telu di Dusun Bayan Beleq, Desa Bayan, Kecamatan Bayan, Kabupaten Lombok Utara - Trisma Hidayanti, Eka; Sudiarna, I Gusti Putu (Humanis; Vol 22 No 1 (2018), 2018)
Wetu Telu people has a life passage rite which is a very sacred gawe pati rite and associated with the ancestor. Gawe pati is a rite for care of the corpses performed with custom and very different from other Lombok society. The aims of this research are to know: (a) how the implementation of gawe pati rite in Wetu Telu of Bayan Village and (b) how is the existence of gawe pati rite in Wetu Telu community.The implementation and existence of the gawe pati rite in the Wetu Telu community can be studied through the transitional rite theory A. Van Gennep and Malinowski's functionalist theory. This study uses ethnographic research methods that include data that is qualitative. The result of research is gawe pati  implementation starting with Selamet Gumi nyusur tanak until nyiu as the closing of the gawe pati procession. Furthermore, the reason for the people of Wetu Telu still maintain the gawe pati rite because they believe in the blessing of the ancestors. The soul of dead relatives will have a good place in the noble realm and can give God blessing to living relatives.The existence of this rite is supported by the existence of internal an eksternal factors. In addition to the factors that support the creation of gawe pati rite, there is also a challenge factor in maintaining the existence of gawe pati rite.